2009
DOI: 10.2478/v10046-009-0044-3
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Consumption in the Latvian Teaching Hospital 2000-2008

Abstract: Antibiotic Consumption in the Latvian Teaching Hospital 2000-2008 Antibiotics are one of the most commonly used drugs in hospital care and significantly contribute to healthcare costs. Recently, there has been significant interest raised on the environmental impact of antibiotic use, in particular on how it effects resistance selection pressure. Rapid global spread of multiresistant bacteria requires improved understanding on how changes in antibiotic use affect resistance selection. We present a uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The findings are comparable with other similar study findings that cefotaxime (a third generation cephalosporin), ampicillin and gentamicin were the most frequently utilized AMAs in the NICUs [12][13][14]. In accordance with this study finding, the drugs belonging to the cephalosporins were found to be the predominantly prescribed AMAs in many of the European hospitals [15][16][17][18].…”
Section: Discussionsupporting
confidence: 91%
“…The findings are comparable with other similar study findings that cefotaxime (a third generation cephalosporin), ampicillin and gentamicin were the most frequently utilized AMAs in the NICUs [12][13][14]. In accordance with this study finding, the drugs belonging to the cephalosporins were found to be the predominantly prescribed AMAs in many of the European hospitals [15][16][17][18].…”
Section: Discussionsupporting
confidence: 91%
“…During the last decade, antibiotics as emerging contaminants are of global concern because antibiotic residues in the environment have the ability to expose the public to serious health hazards. 1 About 100 000-200 000 tons of antibiotics are produced annually for use in animal and human health, agriculture and aquaculture activities, which may aid the antibiotic resistance of microorganisms and destroy the environmental micro-ecosystem. [2][3][4] Sulfonamides are one of the most popular groups of antibiotics that have been used for several decades in both human and veterinary medicine, for therapeutic treatment of infections related diseases.…”
Section: Introductionmentioning
confidence: 99%